Diarrhea in Neonates at the Subdivision of Perinatology Dr. Pirngadi Hospital, Medan - Nurjannah Nurjannah; Guslihan D. Tjipta; Dachrul Aldy; Noersida Raid (Paediatrica Indonesiana, 1991)
A retrospective study on diarrheal manifestation in newborn babies was conducted at the ward of Neonatology, Dr. Pirngadi Hospital Medan from January to December 1988. There were all 3367 babies hospitalized during the study period. One hundred and thirty five (4.0%) had diarrhea, including 106 (78.5%) babies with birth weights of â‰¥2500 gram. Of 2478 babies with spontaneous delivery, 14 (1.4%) babies had diarrhea, while of 889 babies with obstetrical intervention delivery 101 (11.4%) babies had diarrhea. The difference was statistically significant (pL. 0.001). Of 115 babies with diarrhea, there were 81 (60.7%) with moderate and 11 (23.0%) wirh severe dehydration. The mortality rate was 47.5% in patients with accompanying diseases and 0.0% in them without. The mortality rare in babies with birth weights < 1500 gr was 37.9% and 16.9% in babies with birthwejghts â‰¥2500 gram (p<. 0.001). The mortality rste increased with the increase of dehyrotion (p<0.03).